Consumer Buying Decision Process Analysis on Music Live Performances' Tickets - Danil, Dalzi R.; Aprianingsih, Atik (Journal of Business and Management, 2015)
Abstract. The rapid development on live music performances in Indonesia triggered the researcher to think that identifying the factors that influencing consumer buying decision is important more than ever for the industry. There are also lots of live performances that failed because not knowing what factors that made the consumers buy a live performance’s ticket. This research aims to investigate the customer buying decision in music concert event, find the most valuable benefits of music concerts, and which channel of promotion the consumers preferred. To reach the objective, the researcher used buying decision process and marketing mix tools. Respondents’ data that had been collected will have to pass the validity and reliability test. Then, all the data will be processed in descriptive analysis. The results showed that the consumers buy a live music performance’s tickets because of the artist, and the consumers also think that artist be the benefit that they value the most. As for the promotion and distribution channels, it was proven that social media, Instagram to be precise, and promoter’s online ticketing as the most preferred by the consumer.  Keywords: marketing mix, consumer buying decision process, live music performance